IMPLEMENTATION OF DUAL EDUCATION IN UNIVERSITIES OF UKRAINE: SYNERGETIC EFFECTS FOR STAKEHOLDERS - KHOLIAVKO, Nataliia; MELNYCHENKO, Anatolii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The national higher education system needs reform, one of the priority areas of which should be the introduction of dual education. The dual form of education is a form of acquiring professional competences, according to which the student not only goes through educational and industrial practice, but also spends a much larger part of the training period at the enterprise, and not at the university. For this form of organization of education, a tripartite contract is concluded: student - higher education institution - enterprise. During the period of dual education, the student is assigned a mentor from the university and a mentor at the company (with payment for his work as a mentor). The organization of dual education may be problematic for higher education institutions, as it requires updating the normative and methodical base, reviewing the principles and conditions of cooperation with business, finding effective tools for motivating students and academic staff, clarifying the schedule of the educational process, etc. Despite the difficulties and obstacles, dual education needs to be implemented in the activities of Ukrainian universities in view of the set of positive effects obtained from it, namely: reducing the gap between university education and practice, increasing the competitiveness of university graduates on the labor market, simplifying and accelerating the process of their employment, reducing the level of youth unemployment in the country, obtaining the best specialists by entrepreneurs, the possibility of their selection and timely integration into the corporate culture, etc. Dual education requires thorough coordination of higher education institutions, students (if necessary, their parents) and enterprises, as well as support from state and local authorities. At the national level, clear methodological recommendations for the implementation of dual education should be formed; at the level of local authorities - tools to support local businesses involved in dual education; at the level of enterprises - tools to encourage employees to mentor students and providing everything necessary for their education at production Higher education institutions in addition to finalizing regulatory and methodical documentation, should be ready to develop a mechanism for introducing dual education, expand the circle of business partners, encourage them to cooperate according to the duality scheme, as well as develop tools for motivating higher education students. Dual education is also a certain challenge for students, who will have to learn to combine studying at the university with work directly at the enterprise. However, the obvious and powerful advantages of dual education make it one of the key priorities for the development of Ukrainian higher education institutions.
Keywords: dual education; professional competences; higher education system; higher education institution; participants in the educational process; business sector; economic effect